THE BEGINNING AND DEVELOPMENT OF LITHUANIAN PHARMACEUTICAL PERIODICAL IN LITHUANIA TILL THE FIFTH DECADE OF XX CENTURY - STAKULIENĖ, SILVIJA (Knygotyra, 2015)
This article surveys the beginning and development of the Lithuanian pharmaceutical digest since the first decades of the XXth century till the year 1940. The investigative period is divided into two stages: the first covers period 1910–1918, and the second – 1918–1940. “Farmaceutų reikalai” (The pharmacists’ Matters) was published as “Lietuvos žinios” (Lithuanian News) free supplement “Aušrinė” in Vilnius between 1911–1912. The Publisher of “Farmaceutų reikalai” was F. Bortkevičienė, and editress – S. Mošinskaitė. Seven numers were published over two-year period. The publishing was stopped and newspaper sequel “Farmaceutų reikalai” appeared in Moscow in the year 1918. It was published just one number. The Editorial board included such famous people as S. Nasvytis, V. Narbutas, A. Sutkus. The Publisher was Lithuanian Pharmaceutical Union. The significant event was the release of periodical “Medicina ir gamta” (Medicine and Nature) in the year 1913. It was thought to include articles covering pharmaceutical issues, however, the periodal failed to justify the expectations. Five years passed since the incorporation of Lithuanian Pharmacist Society and Lithuanian Pharmaceutical Union issued professional magazine “Farmacijos žinios” (Pharmaceutical News) intended to solve their professional problems. A professional periodical “Farmacijos žinios” was published in the year 1923–1940. A small 2–3 printer’s sheet periodical informed the specialist not only about the newest pharmaceutical and pharmacy achievements in Lithuania and abroad, but also acted as school of professional mastership. Famous Lithuanian pharmaceutical scientists published their articles in this periodical. Four editors Z. Kuzavas (1923–1924), S. Nasvytis (1925–1926, 1930–1929), J. Makauskis (1927–1929), and J. Žemaitis (1935–1940) edited the periodical for 17 years. Three numbers of “Lietuvos farmaceutas” (Lithuanian Pharmacist) were published in the year 1933. It was published by the Lithuanian Pharmacy and Officers Union. The editor was M. Barkauskas, and the number cost 2 Lt. The survey of the four Lithuanian pharmaceutical periodicals that were published at the second and fourth decades of the XXth century allow to resume that those first periodicals were significant and useful. Lithuanian heritage of pharmaceutical periodicals was founded on their bases. The heritage enriched and extended the apprehension of the periodicals that had been published at those times.